(untitled) (Annals of Medical Research, 2024)
Aim: The use of priming fluid in the cardiopulmonary bypass causes hemodilution and increases the need for blood transfusions. Retrograde autologous priming is known to be beneficial in reducing blood transfusion and hemodilution. In this article, 38 cases were retrospectively reviewed to demonstrate the feasibility of routine retrograde autologous priming in a newly established cardiac surgery center. Materials and Methods: A total of 38 patients underwent open-heart surgery between January 2024 and July 2024. All patients were operated using a cardiopulmonary bypass machine primed with retrograde autologous blood. Perfusion and anesthesia techniques were the same for all patients. Hematocrit levels in the preoperative period, during weaning, on the first postoperative day, third day, discharge day, and 10th postoperative day were retrospectively analyzed. Postoperative hemodynamic parameters, pressor requirements, and fluid requirements were recorded. Length of stay in the hospital and intensive care unit, as well as blood requirements, were retrospectively analyzed. Results: No major bleeding and mortality was observed. Hematocrit levels during cardiopulmonary bypass ranged from 28% to 31%. The transfusion rate for per patient was 0.13 units. Conclusion: It was proven that the routine use of retrograde autologous priming, even in a newly established heart surgery institution, is safe, repeatable, and effective in decreasing hemodilution and red cell transfusion rates in cardiac operations.